Culture Metaphor as a Discourse in Public Management: The Case of the Polytechnic University of the Philippines - Sebastian, Raul Roland (Social Sciences and Development Review, 2020)
This research aimed to ascertain the organizational culture of the Polytechnic University of the Philippines. Using the Organizational Culture Assessment Instrument (OCAI), the researcher profiled and assessed the current and the desired culture of the University. Moreover, the Competing Values Framework which is divided into four quadrants wherein each quadrant represents a particular culture type was used by the researcher to analyse the result of the OCAI. The four culture types are as follows; clan which exhibits collegiality and flexibility among members; hierarchy which has high regard to structure and control, both culture types are internally focused; adhocracy which promotes independence and flexibility; and market which focuses on the attainment of the organization’s goals and objectives. The last two culture types are externally focused. This framework provided the researcher an in-depth understanding on the underlying basic assumptions and competing value orientations in the University. The result of the study shows that the dominant current and preferred culture type in the University is the clan culture. The result also suggests that there is no immediate need to change the current cultural values of the PUP community.